Words that work : it's not what you say, it's what people hear - Luntz, Frank I. (Hyperion, 2007)
Communications expert Luntz offers a behind-the-scenes look at how the tactical use of words and phrases affects what we buy, who we vote for, and even what we believe in. Luntz has used his knowledge of words to help more than two dozen Fortune 500 companies grow. He tells us why Rupert Murdoch's six-billion-dollar decision to buy DirectTV was smart because "satellite" was more cutting edge than "digital cable," and why pharmaceutical companies transitioned their message from "treatment" to "prevention" and "wellness." If you ever wanted to learn how to talk your way out of a traffic ticket or talk your way into a raise, this book is for you.--From publisher description.